Psychosis, Socioeconomic Disadvantage, and Health Service Use in South Australia: Findings from the Second Australian National Survey of Psychosis - Sweeney, Shaun; Air, Tracy; Zannettino, Lana; Galletly, Cherrie (Frontiers in Public Health, 2015)
The association between mental illness and poor physical health and socioeconomic outcomes has been well established. In the twenty-first century, the challenge of how mental illnesses such as psychosis are managed in the provision of public health services remains complex. Developing effective clinical mental health support and interventions for individuals requires a coordinated and robust mental health system supported by social as well as health policy that places a priority on addressing socioeconomic disadvantage in mental health cohorts. This paper thus examines the complex relationship between socioeconomic disadvantage, family/social supports, physical health and health service utilisation in a community sample of 402 participants diagnosed with psychosis. The paper utilises quantitative data collected from the 2010 Survey of High Impact Psychosis research project conducted in a socioeconomically disadvantaged region of Adelaide, South Australia. Participants (42% female) provided information about socio-economic status, education, employment, physical health, contact with family and friends, and health service utilisation. The paper highlights that socio-economic disadvantage is related to increased self-reported use of emergency departments, decreased use of general practitioners for mental health reasons, higher body mass index, less family contact and less social support. In particular, the paper explores the multifaceted relationship between socioeconomic disadvantage and poor health confronting individuals with psychosis, highlighting the complex link between socioeconomic disadvantage and poor health. It emphasizes that mental health service usage for those with higher levels of socioeconomic disadvantage differs from those experiencing lower levels of socioeconomic disadvantage. The paper also stresses that the development of health policy and practice that seeks to redress the socioeconomic and health inequalities created by this disadvantage be an important focus for mental health services. Such health policy would provide accessible treatment programs and linked pathways to illness recovery and diminish the pressure on the delivery of health services. Consequently, the development of policy and practice that seeks to redress the socioeconomic and health inequalities created by disadvantage should be an important focus for the improvement of mental health services.